Direct quantitation of amino acids in human serum using a stepwise-dilution strategy and a mixed-mode liquid chromatography-tandem mass spectrometry method - Lee, J.; Lee, S.; Kim, B.; Lee, J.; Kwon, O.-S.; Cha, E. (Korean Society for Mass Spectrometry, 2018)
A quantitation method for free amino acids in human serum was developed using a stepwise-dilution method and a bimodal cation exchange (CEX)/hydrophilic interaction liquid chromatography (HILIC)-tandem mass spectrometry system equipped with an electrospray ionization source (ESI/MS/MS). This method, which was validated using quality control samples, was optimized for enhanced selectivity and sensitivity. Dithiothreitol (DTT) was used as a reducing agent to prevent the oxidation of a serum sample (50 μL), which was then subjected to stepwise dilution using 3, 30, and 90 volumes of acetonitrile containing 0.1% formic acid. Chromatographic separation was performed on an Imtakt Intrada Amino Acid column (50 mm × 3 mm, 3 μm) in mixed mode packed with CEX and HILIC ligands embedded in the stationary phase. Underivatized free amino acids were eluted and separated within 10 min. As a result of the validation, the precision and accuracy for the inter- and intraday assays were determined as 2.11-11.51% and 92.82-109.40%, respectively. The lowest limit of quantification (LLOQ) was 0.5- 4.0 μg/mL and the matrix effect was 80.22-115.93%. The proposed method was successfully applied to the quantitative analysis of free amino acids in human serum. ？ Korean Society for Mass Spectrometry.